(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
Hanging is a type of asphyxia caused by the suspension of the body by a ligature around the neck, with the constricting force being the weight of the body. This method is notably prevalent among young adults as a means of suicide, primarily due to its painless nature and the fact that death typically occurs almost instantaneously, usually within a fatal period of 3–5 minutes. Most patients develop respiratory and neurological complications immediately after their onset. Survival is rare, and those who survive often face delayed complications of hanging, which can occur days or even months after the incident. A case report of a young female who died due to delayed death from hanging occurred 4 months and 2 days after the incident. The patient eventually died due to aspiration pneumonia, which is one of the most fatal complications.